TLC separation of L-tryptophan using microemulsion mobile phase and its spectrophotometric determination - Bhawani, Showkat Ahmad; Sufia, Hena; Ali, Mohammad (NISCAIR-CSIR, India, 2006)
The TLC system comprising silica gel as the stationary phase, and water- in –oil microemul sion (SDS+water+heptane+n-pentanol; (160 g + 8 mL + 16 mL + 25 mL) as the mobile phase, has been identified as the most favourable system for selective separation of L-tryptophan from other amino acids in the presence of metal cation impurities. The proposed method is applicable to the identification and separation of L-tryptophan from drug samples such as Astymin -m (Forte), Astymin (liquid) and Alamin (Forte). The separation up to 10μg of L-tryptophan from milligram quantities (up to 0.77 mg) of other amino acids has also been realized. The quantitative estimation of L-tryptophan by spectrophotometry (λmax 570 nm) after separation from other amino acids has been done. The recovery of tryptophan is around 98% and its limit of detection on silica gel layer is 0.13 μg.